2011
DOI: 10.1007/s11126-011-9182-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Rehospitalization in High-Utilizing Patients in the VA Psychiatric Medical System

Abstract: 233 high-service-utilizing (HSU) psychiatric patients were recruited during an inpatient psychiatric treatment. They completed a questionnaire related to their treatment beliefs and were tracked via computerized medical records over 2 years. During the follow-up period, 79.8% were readmitted for additional inpatient psychiatric treatment. Survival analysis techniques were used to examine patients' rates of readmittance during the follow-up period. Number of previous year inpatient psychiatric days served as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Many disease-specific models fail to account for the multiple comorbidity often witnessed in hospitalized general medical patients. [13][14][15][16][17][18][19][20][21] It is fortunate that increased hospitalization and lengthy hospital stays are useful proxies for disease severity and multiple comorbidities, which are more difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many disease-specific models fail to account for the multiple comorbidity often witnessed in hospitalized general medical patients. [13][14][15][16][17][18][19][20][21] It is fortunate that increased hospitalization and lengthy hospital stays are useful proxies for disease severity and multiple comorbidities, which are more difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies looking at hospital readmissions are disease specific. [13][14][15][16][17][18][19][20][21] There are relatively few studies examining the risk factors for readmission among all primary care patients, and many of these were performed outside the United States or in hospitalist practices. 10,[22][23][24][25] It is well known that a small proportion of patients account for a disproportionate number of hospital admissions and health care costs.…”
mentioning
confidence: 99%
“…On the other hand, a study carried out in the United States 12 showed 79.8% of these patients were new hospitalizations within the two years of follow-up of the research. In Brazil, most researches on the theme do not follow a specific criterion to characterize frequent readmissions, as is the case of studies carried out in Ribeirão Preto 19 and in Rio Grande do Norte 22 , which, in the two-year period, found, respectively, rate of 34 and 60.3% readmissions.…”
Section: Palavrasmentioning
confidence: 91%
“…Other authors considered three or more hospitalizations, whether in a period of 12 8 or 18 9,10 months or up to 5 years 11 . Or, even, combined criteria were used: three or more hospitalizations during a lifetime, at least one hospitalization within the last year and being cared for in the hospital at the beginning of the study 12 . Some of the factors related to the phenomenon are lack or insufficient substitutive and community services and difficulty of adherence to medication and/or outpatient treatment, especially after hospitalization, which, at times, is the way into mental health care [13][14][15] .…”
Section: Palavrasmentioning
confidence: 99%
See 1 more Smart Citation